Application of Chitosan and Citric Acid Coating to Increase The Storage of Marigold Flowers (Tagetes Patula L.) - Emmy Darmawati Darmawati; Aulia Indri Shacrudin (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2023)
Marigold is a flower that can be consumed (edible flower) in fresh condition. Marigold flower damage is characterized by withering and changing the color of the petals to brown (browning). Coating treatment combined with citric acid is expected to be one of the solutions to maintain quality and increase the shelf life of Marigold flowers.. This study aims to examine the effect of citric acid treatment and application of coating made from chitosan on changes in the quality of Marigold flowers as fresh edible flowers. The concentrations of chitosan (K) studied were 0.05% and 0.1%; while the concentration of citric acid (A) was 1% and 2%. Citric acid solution is sprayed first. After air dried, the flowers were sprayed with a coating solution and air-dried. All flower samples, both control and treatment, were packaged and stored at 10oC. During storage, respiration rate, moisture content, weight loss and color were measured. Organoleptic test was carried out by 35 panelists with hedonic values 0-5. The best treatment was A2K2 (2% citric acid and 0.1% chitosan) which was still accepted by the panelists (score 3) until the 6th day of storage with a moisture content of 83.04%, weight loss 21.05%, and the value of °hue 79.70°. A2K2 treatment could increase the shelf life of three days longer than the control.    Keywords:  Chitosan, Citric acid, Coating, Edible flower, Marigold flower.